A Novel Surgical Management for SLAP Lesions in Throwers. Issue 7 (21st July 2017) - Kazutomo, Onishi; Sugaya, Hiroyuki; Takahashi, Norimasa; Matsuki, Keisuki; Tokai, Morihito; Ueda, Yusuke
Objectives: Superior labrum anterior-posterior (SLAP) labrum detachment is frequently seen in throwing athletes and becomes a main cause of internal impingement. Although physical therapy correcting scapular dyskinesis is the first choice of treatment, some requires surgical intervention due to their refractory symptoms. According to recent studies, return rate to pre-injury level in professional baseball players reported 15 to 32%. Currently, most surgeons perform a rigid anterior and postero-superior labrum repair using suture anchors for SLAP detachment. However, we assume that the rigid postero-superior labrum repair cannot have favorable effect on removing pain associated with internal impingement and that this might be the reason for inferior return rate in high-level throwers. Therefore, we do not repair the postero-superior portion, but instead, provide space by debridement in order to eliminate internal impingement. The purpose of this study was to evaluate the outcomes of our surgical management for SLAP lesions in throwers. Methods: Between January 2006 and May 2014, 77 throwing athletes underwent arthroscopic labrum surgeries for their dominant arm. Among them, patients who underwent cuff repair for concomitant PASTA lesions were excluded leaving 65 patients as a candidate for this retrospective study. The aim of surgery is to remove internal impingement by obtaining clearance between the postero-superior glenoid and the rotator cuff. Therefore, we performed debridement for detached postero-superior labrum and repair of antero-superior labrum using 1 or 2 suture anchors, if the detachment was extended to anterior. We analyzed 50 shoulders (77 %), including 11 shoulders only with questionnaire survey, with an average age of 22 (range, 16-44 years). The subjects consisted of 12 professional, 14 collegiate, 15 high school and 9 recreational baseball players with the mean follow-up was 28 months (range, 12-99). Required time for return to pre-injury level and return rate were analyzed. To assess differences between the groups, positions, or athletic levels, student's t-test and one-way analysis of variance were used. Results: All patients demonstrated type II SLAP lesion, and concomitant PASTA lesion was observed in 24 shoulders. Twenty-one shoulders demonstrated stable lesions only with postero-superior labrum detachment; therefore, only arthroscopic debridement was performed for these shoulders (group D). The remaining 29 shoulders demonstrated extensive detachment that involved both anterior and posterior portions; therefore, both debridement for the postero-superior labrum and repair of the antero-superior labrum were performed for these shoulders (group R). Debridement was solely performed for concomitant PASTA lesions. Although 1 patient failed to return to play baseball due to persistent shoulder pain, 49 patients returned to games. Mean times to return to pre-injury level were 9 months (range, 4-20), respectively. Return rate to pre-injury level was 72% overall and 67% in professional baseball players. Mean time and return rate were not significantly different between the groups D and R, positions and athletic levels. Conclusion: Our surgical management for SLAP lesion can provide higher return rate within relatively short time period especially in elite baseball players. Study Year Surgical procedure Patients (# of cases) Return to pre-injury level (%) Kim 2002 Repair Overhead (18) 22% Ide 2005 Repair Baseball (19) 63% Cohen 2008 Repair Prefessional-Baseball (22) 32% Brockmeier 2009 Repair Baseball (11) 64% Neri 2011 Repair Overhead (23) 57% Park 2013 Repair Baseball (16) 38% Fedoriw 2014 Repair Prefessional-Baseball (13) 15% Our study 2016 Debridement w/ or w/o repair Baseball (65) 71% Professional (13) 67%